Risk Appetite, Home Bias and the Unstable Demand for Emerging Market Assets. - Babilis, S; FitzGerald, V (Routledge, 2005)
Home bias arises when the actual portfolio of an investor consists of a smaller proportion of foreign assets than that predicted by standard portfolio theory for the observed set of risks and returns on available assets. The existence and persistence of home bias undermines the theoretical case for the efficiency of international capital markets. In this paper we use data on UK pension fund portfolios to measure home bias, and find that this is doubly acute in the case of emerging market equity--a bias against overseas assets as a whole being further magnified by a bias against emerging markets within the foreign equity class as a whole. Moreover, contrary to the conventional assumption that risk aversion is both relatively low and stable over time (canonized in neoclassical theory by the derivation of constant relative risk aversion from the utility function itself) our finding that home bias fluctuates over time suggests that risk aversion is in fact time-variant and path-dependent. We sketch an alternative Keynesian approach in conclusion.